Strategi Pengembangan Objek Wisata Kolam Renang Tirta Plamboyan Desa Talang Kering Kecamatan Air Napal Kabupaten Bengkulu Utara - Dita Winastia Putri; Siti Hanila; Andriyani Prawitasari (UNIVED Press, 2023)
The Tirta Plamboyan swimming pool tourist attraction which is located in Talang Dry Village, Air Napal District, North Bengkulu Regency is very likely to be developed with adequate resources, but this tourist attraction is not widely known to the outside community and is still lacking in terms of existing facilities. Therefore, the author takes the title